Low Scattering Element-Based Aperture-Shared Array for Multiband Base Stations - Yang, Sheng Jie; Yang, Yang; Zhang, Xiu Yin (IEEE transactions on antennas and propagation, 2021)
This article presents a dual-wideband dual-polarized aperture-shared antenna array with low blockage effect between cross-band elements, including a low-band (LB) element with a 4 × 4 high-band (HB) antenna array underneath. The radiator of the proposed LB element consists of four slim loops with loaded periodic split-ring resonators (SRRs) for achieving low scattering property in the high band. As a result, the blockage effect of the LB element on the HB antenna array is nearly indistinct. The radiation performance, as well as the S-parameters of the HB elements in the dual-band array, is almost the same as the isolated case. For demonstration, the dual-band aperture-shared antenna array, operating in the LB of 0.69-0.96 GHz (32.7%) and the HB of 3.3-4.2 GHz (24%), is fabricated and measured. Besides, the isolated LB antenna and HB array are designed for comparison. Compared with the isolated case, the measured peak gain variation of a 1 × 4 HB array in one column is lower than 0.7 dB after adding the proposed LB element. In addition, the radiation pattern variation within 3 dB beam coverage is less than 1.5 dB. Therefore, the proposed dual-band aperture-shared array is very suitable for tackling the integration of 5G and 4G/3G/2G base station antennas.